Anodic Hydrogen Evolution and Localized Corrosion during Galvanostatic Polarization of a Peak-Aged Mg-Y-Nd-Zr Alloy. Issue 8 (18th May 2016) - Chu, Peng-Wei; Marquis, Emmanuelle A.
Abstract : The hydrogen evolution response on a peak-aged Mg-Y-Nd-Zr (WE43) Mg alloy in a 0.1M sodium chloride (NaCl) solution under galvanostatic polarization is investigated by collecting the evolved hydrogen gas and microstructure characterization techniques. The hydrogen evolution rate increases not only with increasing applied cathodic current density, but also with increasing applied anodic current density, indicative of the so-called negative difference effect (NDE). Localized corrosion is induced by anodic polarization and is the site where rising streams of hydrogen gas evolve. Cross sectional characterization of the regions where localized corrosion initiates reveals inward growth and a porous Mg(OH)2 structure with a finger-like propagation front. Neither a film-free region, nor an enrichment of impurity elements was observed at the localized corrosion regions. In addition, no increase in the cathodic activity was observed when comparing samples with and without prior anodic polarization, indicating that the enhanced catalytic activity of the corrosion product may not play a dominant role in the NDE on peak-aged Mg-Y-Nd-Zr. The relationship between the abnormal hydrogen evolution and the localized corrosion morphology is discussed.